2013
DOI: 10.3233/jad-121171
|View full text |Cite
|
Sign up to set email alerts
|

SPION-Enhanced Magnetic Resonance Imaging of Alzheimer's Disease Plaques in AβPP/PS-1 Transgenic Mouse Brain

Abstract: In our program to develop non-invasive magnetic resonance imaging (MRI) methods for the diagnosis of Alzheimer’s disease (AD), we have synthesized antibody-conjugated, superparamagnetic iron oxide nanoparticles (SPIONs) for use as an in vivo agent for MRI detection of amyloid-β plaques in AD. Here we report studies in AβPP/PS1 transgenic mice, which demonstrate the ability of novel anti-AβPP conjugated SPIONs to penetrate the blood-brain barrier to act as a contrast agent for MR imaging of plaques. The conspic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 92 publications
6
80
0
Order By: Relevance
“…For instance, iron oxide nanoparticles conjugated to vascular cell adhesion molecule 1 (VCAM-1) have been used to enhance MRI of both neuroinflammation and acute cerebral ischemia [26, 27]. Similarly, our group has conjugated SPIONs to antibodies against amyloid in Alzheimer disease plaques to enhance MRI detection of the plaques [28]. We have more recently developed iron-platinum (Fe-Pt) nanoparticles [29] that target ionized calcium binding adaptor molecule 1 (Iba-1) on activated cerebral microglia to directly reveal neuroinflammation.…”
Section: Spions For the Imaging Of Cns Inflammation In Animalsmentioning
confidence: 99%
“…For instance, iron oxide nanoparticles conjugated to vascular cell adhesion molecule 1 (VCAM-1) have been used to enhance MRI of both neuroinflammation and acute cerebral ischemia [26, 27]. Similarly, our group has conjugated SPIONs to antibodies against amyloid in Alzheimer disease plaques to enhance MRI detection of the plaques [28]. We have more recently developed iron-platinum (Fe-Pt) nanoparticles [29] that target ionized calcium binding adaptor molecule 1 (Iba-1) on activated cerebral microglia to directly reveal neuroinflammation.…”
Section: Spions For the Imaging Of Cns Inflammation In Animalsmentioning
confidence: 99%
“…Similarly, in another in vivo study, Sillerud et al reported the targeting efficacy of anti-Ab protein precursor (PP)-conjugated MNPs. These antibody-conjugated MNPs were able to penetrate the BBB and the detectability of the plaques by MRI was higher in AD transgenic mice than control mice [52]. With this approach early diagnosis of the plaques can be done along with direct measurement of efficacy of the antiamyloid therapies.…”
Section: Theranostic Approach Of Mnps For Neurodegenerative Diseasementioning
confidence: 97%
“…The authors could use these nanoparticles to image amyloid plaques by means of μ MRI. Moreover, Sillerud and co-workers could show that conjugation of an anti-amyloid β antibody to iron oxide nanoparticles enabled binding of nanoparticles and contrast enhanced imaging of Alzheimer ' s amyloid plaques (49) .…”
Section: Functionalization With Watersoluble Nanoparticlesmentioning
confidence: 99%